2016
DOI: 10.1017/s004393391600026x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the crop in poultry production

Abstract: The importance of the crop is often underestimated in poultry production. In addition to storing ingested feed, it also can impact nutrient digestion by digesta softening and the initial activity of feed (endogenous and exogenous) and microbial enzymes. The crop represents the first major defence against poultry pathogens and zoonotic organisms with well established adaptive and innate immune function, and a lactobacilli dominated microbiota capable of reducing the passage of these organisms further along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 97 publications
3
42
0
3
Order By: Relevance
“…Crop digesta pH depends, at least in part, on the fermentation capability of the microbial population and the concomitant increase in organic fatty acid production in this organ. The fermentation activity of the crop is expected to increase with age ( Classen et al., 2016 ), and consequently, the pH of the crop might decrease with age, which is in agreement with the results reported herein.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Crop digesta pH depends, at least in part, on the fermentation capability of the microbial population and the concomitant increase in organic fatty acid production in this organ. The fermentation activity of the crop is expected to increase with age ( Classen et al., 2016 ), and consequently, the pH of the crop might decrease with age, which is in agreement with the results reported herein.…”
Section: Discussionsupporting
confidence: 91%
“…Longer retention times of the digesta in the crop are associated with more nutrients available for fermentation and with an increase in the activity of the microbiota present in this organ ( Svihus et al., 2013 , Classen et al., 2016 ). Consequently, a reduction in crop pH was expected as the length of the fasting period increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phytase activity in the crop content was identical to that of the small intestine of laying hens aged 47 weeks when measured per gram of digesta [ 26 , 27 ]. Possibly, the relatively short retention time in the crop when feed is offered for ad libitum consumption [ 28 , 29 ] leads to an insignificant degradation of InsP 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was investigated, where it was found that providing birds with daily physical access to feed for intervals of 12, 16, and 20 h did not influence lysine HCl utilisation in broiler chickens [134]. The basis for this appears to lie in the capacity of birds to 'crop-up' via anticipatory feeding and retention of digesta in the crop [135]. Instructively, reducing feeding frequencies from 20 h to 16 and 12 h influenced the relative crop weights (p < 0.001), with increases from 3.8 g/kg to 5.5 and 7.7 g/kg [134].…”
Section: Lysinementioning
confidence: 99%